Public Policy Advocacy Strategies In Eradication Of Illegal Parking - Nasrullah, Nasrullah (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2025)
his study aims to examine issues such as what factors cause the rampant illegal parking in Pamekasan Regency, what effective policy advocacy strategies are for regulating illegal parking, and who should be involved in this advocacy process. This is based on the increasing number of motorized vehicles in Pamekasan Regency and limited parking facilities, which have given rise to various problems, one of which is the prevalence of illegal parking in several strategic locations in the city. This situation demonstrates the need for more effective parking management and regulation policies, supported by policy advocacy strategies involving various stakeholders. This research used a literature review method. The goal is to build a theoretical foundation, strengthen arguments, and identify gaps in previous research. This method involves systematic reading, recording, and processing of literature to support research findings. Based on the parking policy evaluation, the first problem arises from the prevalence of illegal parking in urban areas, particularly in Pamekasan Regency. This is quite complex and has multidimensional impacts. Second, illegal parking also results in losses to Regional Original Income (PAD). Third, this phenomenon contributes to social conflict within the community. Fourth, the prevalence of illegal parking contributes to the degradation of urban spatial planning. Therefore, the Pamaekasan Regency Government needs to take strategic steps to advocate for policies. Controlling illegal parking requires a comprehensive approach involving various key aspects, including regulation, education, infrastructure, cross-sector coordination, and human resource empowerment. This strategy aims to strengthen the legal framework, raise public awareness, and create orderly and sustainable parking governance. Public policy advocacy strategies can significantly contribute to stronger and more publicly accepted law enforcement. With public support, clear regulations, and increased officer capacity, district governments can crack down on illegal parking more effectively and sustainably.